New method for the investigation of mode coupling in graded-index polymer photonic crystal fibers using the Langevin stochastic differential equation - Savović, Svetislav; Djordjevich, Alexandar; Aidinis, Konstantinos; Chen, Chen; Min, Rui (Frontiers in Physics, 2024)
The mode coupling in a graded-index polymer photonic crystal fiber (GI PPCF) with a solid core has been investigated by means of the Langevin equation. Based on the computer-simulated Langevin force, the Langevin equation is numerically integrated. The Langevin equation's numerical solution and the time-independent power flow equation's (TI PFE) numerical solution agree. We have shown that by solving the Langevin equation which is a stochastic differential equation, one can successfully treat a mode coupling in GI PPCFs, which is intrinsically stochastic process. We have demonstrated that, in terms of effectiveness, the Langevin equation is preferable compared to TI PFE. The GI PPCF achieves the equilibrium mode distribution (EMD) at a coupling length that is even shorter than the conventional GI plastic optical fiber (POF). The application of multimode GI PCFs in communications and optical fiber sensor systems will benefit from these findings.